Practical training report: Muar District Office (MDO) / Muhammad Asif Abdul Rahman - Abdul Rahman, Muhammad Asif (Universiti Teknologi MARA, Sarawak, 2016)
Organization can be defined as a unit of people who have capabilities to manage all the work process according to their duties in order to meet organizational goal. Structure of management determines the relationship between different activities and the members, responsibility, subdivides and assigned roles to carry out different duties. (Business Dictionary.com, n. da) In Muar District Office, its building was built in year 1884. This building was manufactured by wood under the control of Dato’ Bentara Luar, Dato’ Mohd Salleh Bin Perang (Muar District Office, 2005a).This woody building has endured for 31 years until the year 1915 (Muar District Office, 2005b). The resident of British government had made a decision to replace the building with the new one and made it as Muar District Office which has existed until today (Muar District Office, 2005c). During World War 2, this kind of building had been conquered by Japanese army (Muar District Office, 2005d). Even, though its function had been fixed but the pattern of the administrative system was following the Japanese culture (Muar District Office, 2005e). After the end of World War, this building and the administration of Muar District, had been taken over by the British governance and State Government ofJohor (Muar District Office, 2005f). Since the Malaysian Independence, this building has been possessed and administered by Johor State Government (Muar District Office, 2005g).